Whole genome duplication in oral squamous cell carcinoma in patients younger than 50 years: implications for prognosis and adverse clinicopathological factors. Issue 9 (24th June 2022) - Satgunaseelan, Laveniya; Strbenac, Dario; Willet, Cali; Chew, Tracy; Sadsad, Rosemarie; Wykes, James; Low, Tsu‐Hui (Hubert); Cooper, Wendy A.; Lee, C. Soon; Palme, Carsten E.; Yang, Jean Y. H.; Clark, Jonathan R.; et al.
Abstract: Introduction: Oral squamous cell carcinoma (OSCC) in the young (<50 years), without known carcinogenic risk factors, is on the rise globally. Whole genome duplication (WGD) has been shown to occur at higher rates in cancers without an identifiable carcinogenic agent. We aimed to evaluate the prevalence of WGD in a cohort of OSCC patients under the age of 50 years. Methods: Whole genome sequencing (WGS) was performed on 28 OSCC patients from the Sydney Head and Neck Cancer Institute (SHNCI) biobank. An additional nine cases were obtained from The Cancer Genome Atlas (TCGA). Results: WGD was seen in 27 of 37 (73%) cases. Non‐synonymous, somatic TP53 mutations occurred in 25 of 27 (93%) cases of WGD and were predicted to precede WGD in 21 (77%). WGD was significantly associated with larger tumor size ( p  = 0.01) and was frequent in patients with recurrences (87%, p  = 0.36). Overall survival was significantly worse in those with WGD ( p  = 0.05). Conclusions: Our data, based on one of the largest WGS datasets of young patients with OSCC, demonstrates a high frequency of WGD and its association with adverse pathologic characteristics and clinical outcomes. TP53 mutations also preceded WGD, as has been described in other tumors without a clear mutagenic driver.